Nutritive value of forages as affected by soil and climatic differences - Clary, F.G.; Brent, B.E.; Richardson, D.; Erhart, A.B.; Banbury, Evans E.; Boren, Fred W. (Kansas State University. Agricultural Experiment Station, 2011)
Effects of environment on the performance of beef steers in Kansas have been studied since 1962. The experiments, in three phases, have included seven feedlot trials and one digestion trial.
Keywords: Beef; Nutritive value; Soil; Climate